CLASSROOM ACTION RESEARCH: EFFORTS TO IMPROVE LEARNING OUTCOMES BY APPLYING DIFFERENTIATED LEARNING-BASED INQUIRY LEARNING MODELS - Nurhidayat, Wahyu; Rusnayati, Heni; Anisah, Ai; Iriyanti, Puri Irna (Journal of Teaching and Learning Physics, 2023)
Based on the results of the preliminary study it is known that learning activities still use conventional learning and pay little attention to student learning characteristics. This certainly affects student learning outcomes. This study aims to improve student learning outcomes by applying an inquiry learning model based on differentiation learning strategies. This type of research is Classroom Action Research (CAR). The subjects of this study were 31 students of class XI MIPA 1 with an age range of 16-17 years. Data collection techniques used are observation and tests. The results of the study stated that classical completeness in cycle I was 29% and increased in cycle II which obtained mastery of 87%. Therefore, it can be concluded that the inquiry learning model based on differentiation learning strategies can improve student learning outcomes. The research results have implications in providing an overview for improving the quality of learning, especially within the scope of learning in the classroom.